Nasal lavage microbiome, but not nasal swab microbiome, correlates with sinonasal inflammation in children with cystic fibrosis - Chung, Jaehi; Boutin, Sébastien; Frey, Dario; Joachim, Cornelia; Mall, Marcus A.; Sommerburg, Olaf (Journal of cystic fibrosis, 2024)
Background - Cystic fibrosis (CF) is characterized by highly viscous mucus obstructing the lower and upper airways, chronic neutrophil inflammation and infection resulting not only in lung destruction but also in paranasal sinus involvement. The pathogenesis of CF-associated chronic rhinosinusitis (CRS) is still not well understood, and it remains unclear how the microbiome in the upper airways (UAW) influences paranasal sinus inflammation. - Methods - In a cross-sectional study in pediatric patients with CF under stable disease conditions, we examined the microbiome in relation to inflammation by comparing nasal swabs (NS) and nasal lavage (NL) as two UAW sampling methods. The microbiota structure of both NS and NL was determined by 16S rRNA gene amplicon sequencing. In addition, pro-inflammatory cytokines (IL-1β, IL-6, IL-8, TNF-α) and proteases (SLPI, TIMP-1, NE/A1-AT complex) as well as neutrophil elastase activity were measured in NL. - Results - Simultaneous NS and NL samples were collected from 36 patients with CF (age range: 7 - 19 years). The microbiome of NS samples was shown to be significantly lower in α-diversity and evenness compared to NL samples. NS samples were particularly found to be colonized with Staphylococcus species. NL microbiome was shown to correlate much better with the sinonasal inflammation status than NS microbiome. Especially the detection of Moraxella in NL was associated with increased inflammatory response. - Conclusion - Our results show that the NL microbiome reflects sinonasal inflammation better than NS and support NL as a promising tool for simultaneous assessment of the UAW microbiome and inflammation in children with CF.